Automations, Technological and Nervous: Addiction Epidemics from Athens to Fake News - Moore, Gerald (New Formations, 2019)
Building on work by Bertrand Gille (1978), Bernard Stiegler argues that waves of technological automation tend to be characterised by periods of social 'disadjustment', when the rapid pace of change leaves political and social support systems inadequate to the task of ensuring societal cohesion. In the absence of adequate rules for the government of consumption, we can see this technological disadjustment symptomatised in a phenomenon of 'generalised addiction'. We are living through one such period, struggling in the wake of disintegrating older social norms, and prior to the birth of new ones better able to mitigate the toxic potential of our technological pharmaka . But emerging work in addiction research facilitates the argument, made here, that epidemics of generalised addiction are not unique to the digital era. The works of Plato can be interpreted as a response to an addiction epidemic in fifth-century Athens, which was attributable, in turn, to the technological revolution of alphabetic writing. The comparison of then and now, two periods of technological change bringing political turmoil, throws up multiple parallels with the ongoing transformations of digital culture. Athenian symposia functioned as sanctuaries where aristocrats, displaced from their traditional position at the heart of an increasingly chaotic city, retreated to experiment with religious, poetic and pharmaceutical oblivion. They accordingly bring to mind both the anxiety-relieving 'zones' of escape and disavowal sought out by addicts in using, and the internet echo chambers into which we retreat from an increasingly fragmented public sphere. In a move that hints at an exit strategy for our own period of generalised addiction, Plato builds on the logical thinking made possible by the new technology of writing to reinvent and readjust a dislocated political morality.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzg5OC9uZXdmOjk4LjA4LjIwMTk